Root knot nematode in ornamental plants of Mazandaran Province North of Iran - Mahdavian, Seyed Esmaeil; Jahanshahi, Farahnaz (International Journal For Research In Agricultural And Food Science, 2017)
170 samples of soil, root and standing parts of ornamental greenhouses plant collected from different city of Mazandaran province which included Amol (7 samples), Tonekaboon (23 samples), Ramsar (21 samples), Salmanshahr ( 9 samples),KelarAbad ( 24 samples), AbasAbad ( 34 samples), Nashtarood (9 samples), Nowshahr (34 samples), Hachirood (9 samples).These samples collected from 74 flowers and ornamental plants that belong to the 50 different groups of plant and collected between the years of 2012-2015 and then investigated. From 170 collected samples of soil and roots, Meloidogyne javanica nematode that produce knots roots have 28.5 frequency percent and it was the most popular species in ornamental greenhouse of Mazandaran. Meloidogyne javanica has 43 frequency percent in Amol and 117 nematodes, in Abas-abad it has 18 frequency percent and 670 nematodes, in Salmanshahr it has 25 frequency percent and maximum population of 1140, in Kelar-abad it has 10 frequency percent and 40 nematodes, in Hachirood it has 33 frequency percent 170 nematodes, in Nowshahr it has 57 frequency percent and maximum nematodes of 2520, in Abas-abad it has 42 frequency percent and maximum population of 110 nematodes, in Ramsar it has 52.4 frequency percent and its maximum percent was 1560 nematode that is separated from 250 cm3 of soil.